SUSTAINABLE DEVELOPMENT GOALS AND ELIMINATION OF CHILDREN'S MARRIAGE PRACTICE IN INDONESIA - Sonny Dewi Judiasih; Luh Putu Sudini; Betty Rubiati; Deviana Yuanitasari; Hazar Kusmayanti; Elycia Feronia Salim (NOTARIIL Jurnal Kenotariatan, 2019)
Empowerment of women and girls is to be realized through sustainable development. Sustainable development depends on an equitable distribution of resources and it cannot be achieved without gender equality (Pathania, 2017). This research aims to analyze the implementation of the Sustainable Development Goals Program in the elimination of child marriage practices in Indonesia and to discover efforts to implement the Sustainable Development Goals Program by government officials in the elimination of child marriages in Pesisir Selatan District, West Sumatra Province. This research used the Sustainable Development Goals approach. To obtain the data, the researchers used primary and secondary data. Based on the result, it can be concluded that implementation of achievement of the Sustainable Development Goals is not only carried out centrally by the central government, but the central government also submits this to the regional government.